Dynamic non-reciprocal meta-surfaces with arbitrary phase reconfigurability based on photonic transition in meta-atoms - Shi, Yu; Fan, Shanhui (Applied physics letters, 2016)
We introduce a distinct class of dynamic non-reciprocal meta-surfaces with arbitrary phase-reconfigurability. This meta-surface consists of an array of meta-atoms, each of which is subject to temporal refractive index modulation, which induces photonic transitions between the states of the meta-atom. We show that arbitrary phase profile for the outgoing wave can be achieved by controlling the phase of the modulation at each meta-atom. Moreover, such dynamic meta-surfaces exhibit non-reciprocal response without the need for magneto-optical effects. The use of photonic transition significantly enhances the tunability and the possible functionalities of meta-surfaces.